WHAT CAUSES PATRONAGE REFORM? IT DEPENDS ON THE TYPE OF CIVIL SERVICE REFORM. (8th September 2016) - SCHUSTER, CHRISTIAN
Abstract : Public employment in most developing countries is governed by political patronage. Patronage provides many incumbents with governability and electoral advantage. What causes governments to forsake patronage in favour of civil service reform? This article reviews scholarly explanations. It finds that studies usefully identify diverse socioeconomic and political‐institutional factors which can affect reform incentives. The causal effects of these factors – their weight, mechanisms and signs – are contested, however. This article partially resolves this contestation by considering which reform studies explain: different bureaucratic structures develop asynchronously and feature different determinants. To illustrate, political competition is argued to incentivize reform to 'blanket in' party appointees; or do the opposite by reducing expectations to reap longer‐term state capacity benefits. Yet, 'blanketing in' necessitates bureaucratic job stability, while state capacity requires merit recruitment of skilled bureaucrats – two poorly correlated reforms. The causes of patronage reform thus depend on the type of civil service reform.